Раритетні дендроекзоти відділу Pinophyta у Державному дендрологічному парку “Тростянець” НАН України - Medvedev, V.A.; Iljenko, O.O. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2015)
The results of specific composition, geographical origin and viability of rarity plants of Pinophyta included in the world red lists and Red book of Ukraine, in the conditions of dendropark Trostjanets are shown. Based on the metho dology of integral outphytosozological evaluation, species of rarity dendroecsotic plants were given the phytosozological descriptions. 56 species of rarity dendrosozoecsotic plants of Pinophyta in 2008 are grown on territory of dendropark. The majority (76.8 %) of this species have natural habitats in the floristic areas of the Boreal subkingdom, 41.1 % of the rarity species originate from Circumboreal floristic area. The investigated species substantially differentiated after the level of geographical distribution: 45 species have limited natural habitats related to one or two floristic areas, many of them are endemic or subendemic species, 11 species have geographical amplitude and originated from three and more floristic areas. The rarity dendroecsotic plants of the park belong to three outphytosozological classes (III–V), their outphytosozological index – from 9 to 22. Picea maximowiczii Regel ex Mast., Cryptomeria japonica (Thunb. ex L.f.) D. Don and Picea alcoquiana (Veitch ex Lindl.) Carrière have maximal values, Thuja occidentalis L, T. plicata Donn ex D. Don, Pinus nigra J.F.Arnold, Picea glauca (Moench) Voss and others species, that have the greatest regional representativeness, – minimal values.